'Debtors to the Spirit' in Romans 8.12? Reasons for the Silence. (14th December 2012) - Gieniusz, Andrzej
Abstract : This article discusses the Pauline anacoluthon in Romans 8.12. The usual interpretations consider it a communicative accident on the part of Paul or as a case of laudable laconicism. Against such an understanding the present author proposes to consider the anacoluthon as a figure of speech, deliberately chosen by the Apostle both to emphasize the total character of the filial relationship of Christians to God, as opposed to their past dependences, and to help them discover this particularity of their new status on their own.